2011
DOI: 10.1063/1.3642087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnO nanoparticles on the SmC*-SmA* phase transition temperature in electroclinic liquid crystals

Abstract: Experimental assessment of quasi-binary picture of thermotropics: Induced smectic A phase in 7CB-n-heptane system J. Chem. Phys. 135, 044705 (2011) Does transparent nematic phase exist in 5CB/DDAB/water microemulsions? From the viewpoint of temperature dependent dielectric spectroscopy J. Chem. Phys. 134, 034505 (2011) A kind of two-dimensional electroconvection at ultralow electric frequency Appl. Phys. Lett. 97, 203507 (2010) Study of the isotropic to smectic-A phase transition in liquid crystal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The helical dynamical process is a debatable research problem as it is demonstrated in selected FLC samples and needs more rigorous theoretical and experimental studies. However, this type of mode was also observed by our group earlier in some of the FLCs such as water-added FLC [9], pure FLC (KCFLC 7S), which becomes dominating when gold nanoparticles are added to it [10], and in ZnO-added electroclinic liquid crystal [11]. All these measurements were performed at 500-mV ac (alternating current) voltage of probing signal from an impedance analyzer.…”
Section: Introductionsupporting
confidence: 54%
“…The helical dynamical process is a debatable research problem as it is demonstrated in selected FLC samples and needs more rigorous theoretical and experimental studies. However, this type of mode was also observed by our group earlier in some of the FLCs such as water-added FLC [9], pure FLC (KCFLC 7S), which becomes dominating when gold nanoparticles are added to it [10], and in ZnO-added electroclinic liquid crystal [11]. All these measurements were performed at 500-mV ac (alternating current) voltage of probing signal from an impedance analyzer.…”
Section: Introductionsupporting
confidence: 54%
“…1,2 Moreover, investigations demonstrating the suppressed ionic effect by nanodopants have also been clarified for solving image problems in LC displays caused by ubiquitous impurity ions. [3][4][5][6][7] Depending on the intrinsic characteristics of the dopant and mutual interaction with LC molecules, researchers have studied the individual effects of nanomaterial additives on the behaviors of phase transitions in LCs in terms of the molecular ordering, 8,9 dielectric relaxation, 10 and electrophysical properties of LCs. [11][12][13] Among currently available nanomaterials, graphene, classified as a two-dimensional (2-D) carbon allotrope, has attracted immense attention for potential applications in electronic devices and nanocomposites since its successful isolation in 2004.…”
mentioning
confidence: 99%
“…Coming on metallic NPs, ZnO NPs find use in a wide range of technologically important areas of LCs due to simple production, large band gap energy, high exciton binding energy and excellent piezoelectric properties at room temperature. Additionally, a decrease in the threshold voltage, lower energy consumption, controlled orientation and increased phase transition temperature of LCs-ZnO composites is reported [9,14,29,32]. It is also observed that a decrease in the threshold voltage with dispersion of ZnO NPs is resulted by suppressing undesired field screening effects due to reduced moving ion density [13].…”
Section: Introductionmentioning
confidence: 86%